2010
DOI: 10.1016/j.exppara.2009.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania (Leishmania) infantum/chagasi: Histopathological aspects of the skin in naturally infected dogs in two endemic areas

Abstract: In the New World, visceral leishmaniasis (VL), which is a progressive disease and frequently fatal, is caused by Leishmania (Leishmania) infantum/chagasi. It is endemic in many regions of Brazil and occasionally occurs in non-endemic regions when dogs from an endemic area are introduced. The aim of the present study is to compare different skin infection patterns of dogs from two leishmaniasis endemic areas. A histological analysis of dogs from Campo Grande, Mato Grosso do Sul state, a region where epidemic ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
7
0
3
Order By: Relevance
“…This finding could be related to this cell type being involved in attempts to contain the intense skin parasite density, as described in several studies that evaluated a murine model [41][43]. Calabrese et al [21] described an intense inflammatory skin reaction formed mainly by mast cells, indicating that these cells might exert a role in innate immunity against L. infantum infection. Our data regarding mast cells conflict with this possibility, however.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This finding could be related to this cell type being involved in attempts to contain the intense skin parasite density, as described in several studies that evaluated a murine model [41][43]. Calabrese et al [21] described an intense inflammatory skin reaction formed mainly by mast cells, indicating that these cells might exert a role in innate immunity against L. infantum infection. Our data regarding mast cells conflict with this possibility, however.…”
Section: Discussionmentioning
confidence: 75%
“…Calabrese et al [21] evaluated histopathological aspects of the skin in naturally infected dogs and showed that low parasite load is associated with an intense inflammatory reaction driven mainly by mast cells, indicating that these cells exert a role in innate immunity and in the resistance against canine Leishmania infection.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of more than one inflammatory pattern, mixed inflammatory patterns, or an overlapping of histological patterns may be observed in L. infantum infections in dogs (Torres et al, 2008). CVL leads to diverse clinical and histological manifestations and the latter mostly demonstrates mild to marked inflammatory infiltrates, depending on host resistance variations (Calabrese et al, 2010). These findings may change due to cutaneous coinfections and concomitant diseases (Gross et al, 2005), such as dermatophytosis fungal, observed in 64.7% of L. infantum positive dogs herein, or hypothyroidism, where the characteristics were more suggestive of atrophic dermatoses than that of parasitic dermatoses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using MC-deficient Kit W-sh / Kit W-sh mice for infection with L. major promastigotes results in a worse disease outcome, e.g., significantly enhanced lesion progression and lesional parasite burdens, accompanied by significantly decreased levels of IFN-γ and IL-17A, but significantly increased IL-4 and IL-10, compared to wild-type mice, indicating that MCs play a crucial role against Leishmania parasites by promoting Th1 and Th17 responses in vivo (26). L. infantum / chagasi -infected skins, from dogs of two different leishmaniasis endemic areas of Brazil, showed different skin infection patterns; however, dogs from both areas showed dermic inflammatory infiltrates composed of numerous degranulated MCs compared to normal skin, indicating that MCs modulate the immune response and participate in the host defense against Leishmania infection (27). Dogs naturally infected with L. infantum showed increased inflammatory infiltrates in the skin of animals with severe forms of canine visceral leishmaniasis and a high parasite density.…”
Section: Mcs In Leishmania Spp Infectionmentioning
confidence: 99%